The New Encyclopaedia Britannica (Vol.15) : Macropaedia : Knowledge In Depth : Birds Chess - Encyclopaedia Britannica, Inc. (Chicago Encyclopaedia Britannica, 2005)
Provides access to quick facts, articles on various subjects, along with images of art, geography, science, sports, and more
Include Color Illustration
Keywords: Encyclopedias and dictionaries